2023
DOI: 10.1038/s41598-023-33076-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of bulk lipid species in human platelets and their thrombin-induced release

Abstract: Lipids play a central role in platelet physiology. Changes in the lipidome have already been described for basal and activated platelets. However, quantitative lipidomic data of platelet activation, including the released complex lipids, are unavailable. Here we describe an easy-to-use protocol based on flow-injection mass spectrometry for the quantitative analysis of bulk lipid species in basal and activated human platelets and their lipid release after thrombin activation. We provide lipid species concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
1
0
0
Order By: Relevance
“…The following platelet aggregation was found to be accompanied by the significant deregulation of 786 proteins, as well as 28 fatty acids and lipid mediators in the platelet supernatant (Figure , Supplementary Table S7). Most of these findings are compatible with or reproduce the results of previous reports. , As expected, all proteins except antibodies with increased abundance values in serum, when compared to those in plasma, were also found to be released from platelets upon aggregation. Similarly, most eicosanoids with high abundance values in serum were found to be released from platelets upon aggregation (Supplementary Table S8).…”
Section: Resultssupporting
confidence: 92%
“…The following platelet aggregation was found to be accompanied by the significant deregulation of 786 proteins, as well as 28 fatty acids and lipid mediators in the platelet supernatant (Figure , Supplementary Table S7). Most of these findings are compatible with or reproduce the results of previous reports. , As expected, all proteins except antibodies with increased abundance values in serum, when compared to those in plasma, were also found to be released from platelets upon aggregation. Similarly, most eicosanoids with high abundance values in serum were found to be released from platelets upon aggregation (Supplementary Table S8).…”
Section: Resultssupporting
confidence: 92%
“…Nevertheless, critical precursors for platelet signaling like PI 18:0_20:4 are already abundantly available in MKs. Comparing fully mature MKs against the lipidome of human 31 and mouse 12 platelets reveals an equal basis for various lipid classes such as PE, PS, ST, cholesterol ester (SE), PC-ether lipid (PCO), triacylglycerol (TG) and lyso-PE (LPE) (Fig. 2e).…”
Section: Articlementioning
confidence: 99%
“…GPLs are the predominant phospholipids found in mammalian cell membranes and fulfill critical functions across diverse physiological processes, such as cell signaling, platelet activation, endoplasmic reticulum regulation, and mitochondrial stress management [ 17 , 18 ]. Animal studies have suggested that the imbalance in PC and PE and their ratios might contribute to multiple metabolic disorders, such as endoplasmic reticulum stress, obesity, and insulin resistance [ 19 21 ].…”
Section: Discussionmentioning
confidence: 99%